2017
DOI: 10.3904/kjim.2015.394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on hyperglycemia in an experimental model of tacrolimus- and sirolimus-induced diabetic rats

Abstract: Background/AimsMetformin (MET) is a first-line drug for type 2 diabetes mellitus (DM); its effect on new-onset diabetes after transplantation caused by immunosuppressant therapy is unclear. We compared the effects of MET on DM caused by tacrolimus (TAC) or sirolimus (SRL).MethodsDM was induced by injection of TAC (1.5 mg/kg) or SRL (0.3 mg/kg) for 2 weeks in rats, and MET (200 mg/kg) was injected for 2 more weeks. The effects of MET on DM caused by TAC or SRL were evaluated using an intraperitoneal glucose tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
4
23
0
Order By: Relevance
“…In accordance with literature, the doses of sitagliptin and metformin (10 mg/kg and 200 mg/kg, respectively) were selected from the low end of the ranges used in previous studies [16][17][18], in order that a potential synergistic effect could be detected and to avoid metformin toxicity if given ≥600 mg/kg/day [19]. The dose of medications was adjusted every week, according to the body weight changes to keep a similar dose per kg body weight of rat, over the whole period of treatment, for each group.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with literature, the doses of sitagliptin and metformin (10 mg/kg and 200 mg/kg, respectively) were selected from the low end of the ranges used in previous studies [16][17][18], in order that a potential synergistic effect could be detected and to avoid metformin toxicity if given ≥600 mg/kg/day [19]. The dose of medications was adjusted every week, according to the body weight changes to keep a similar dose per kg body weight of rat, over the whole period of treatment, for each group.…”
Section: Experimental Designmentioning
confidence: 99%
“…Biology 2020, 9, x FOR PEER REVIEW 4 of 26 mg/kg/day [19]. The dose of medications was adjusted every week, according to the body weight changes to keep a similar dose per kg body weight of rat, over the whole period of treatment, for each group.…”
Section: Hfd Feedingmentioning
confidence: 99%
“…3 The pathogenesis of Tac-induced diabetes mellitus (DM) is unclear, but we and others reported that the direct toxic effect of Tac on pancreatic beta cells and oxidative stress has a pivotal role in Tac-induced DM. [4][5][6] Ginseng, a traditional medicine, is commonly used to modulate immune functions and metabolism, and ginsenosides are the pharmacologically active components in ginseng and that are used as traditional medicine to treat various diseases. 7 Korean red ginseng extract (KRGE) is a popular and commercially available health food, but its mechanism is still undetermined.…”
mentioning
confidence: 99%
“…It improves plasma levels of glucagon-like peptide 1 (GLP-1), peripheral and liver sensitivity to insulin, decreases hepatic glucose production, and causes weight reduction (21). A recent study demonstrated that metformin stimulates the adenosine monophosphate protein kinase signaling pathway (22). Lee et al reported that phosphorylation of AMPK signaling levels is diminished in the diabetesinduced renal hypertrophy (23).…”
Section: Discussionmentioning
confidence: 99%